Accelerated LCF‐creep experimental methodology for durability life evaluation of turbine blade. Issue 5 (4th January 2018) - Shi, D.; Li, Z.; Yang, X.; Wang, H.
Abstract: This paper proposes an accelerated low cycle fatigue (LCF)‐creep experimental methodology in laboratory to investigate the durability life of turbine blades. A typical mission profile of the turbine blade was obtained by means of rain flow counting method, considering both the actual flight condition and ground test data. Finite element analysis (FEA) was conducted to obtain the stress and temperature fields of turbine blade. A test system was constructed to conduct LCF‐creep experiments of turbine blades, simulating the stress and temperature distributions of critical section properly. LCF‐creep experiments of full‐scale turbine blades were performed under a trapezoidal loading spectrum. Experiment results showed that the durability life of turbine blade based on numerical method was longer than that based on this experimental methodology, even an order of magnitude. Furthermore, this experimental methodology helped to extend the service life of this blade safely, and its validity was verified in actual service condition.